Pediatric hematology/oncology physician and nurse practitioner attitudes towards the COVID-19 vaccines: A qualitative study - Meagan E. Miller; Mahvish Q. Rahim; Scott L. Coven; Seethal A. Jacob; Gregory D. Zimet; Carolyn G. Meagher; Mary A. Ott (Taylor & Francis Group, 2022)
As of 05/28/2021, SARS-CoV-2 (COVID-19) had caused 3.9 million infections in the United States (US) pediatric population since its discovery in December of 2019. The development and expansion of vaccination has markedly changed the shape of the epidemic. In this qualitative study, we report on pediatric hematology/oncology provider views on the COVID-19 vaccine prior to approval in the adolescent population <16 years of age. Results from interviews with 20 providers across the state of Indiana showed that most were supportive of the COVID-19 vaccine for healthy adults. However, the majority also expressed a need to see more data on the safety and effectiveness of COVID-19 vaccinations in pediatric hematology/oncology populations. While they recognized the public health importance of vaccination, their duty to protect their patients led to a need for more specific safety and efficacy data.